3‐D visualisation, printing, and volume determination of the tracheal respiratory system in the adult desert locust, Schistocerca gregaria. Issue 1 (July 2014) - Greco, Mark; Bell, Duncan; Woolnough, Lewis; Laycock, Stephen; Corps, Nick; Mortimore, David; Hudson, Diana
Abstract Here, we describe a single micro‐CT scan with a spatial resolution of 10 μm of a 10‐day‐old adult male Schistocerca gregaria (Forskål) (Orthoptera: Acrididae) and we compare our tracheal volume (VT) determination with published work on the subject. We also illustrate the feasibility of performing non‐invasive 'virtual dissection' on insects after performing micro‐CT. These post‐processing steps can be performed using free downloadable 3‐D software. Finally, the values of producing stereo‐lithography (STL) files that can be viewed or used to print out 3‐D models as teaching aids are discussed.